Augustine's Criteria for Nonliteral Interpretation: A Reconsideration - Milad, Corine (Augustiniana, 2025)
The aim of this article is to demonstrate that Augustine’s criteria for nonliteral interpretation are intended partly to safeguard Scripture’s literal referent and therefore also to offer a critique of earlier allegorical exegesis. First, I discuss Augustine’s absurdity criterion (and its concomitant, charity criterion): if a text is absurd according to the letter (ad litteram), the reader must interpret figuratively (figurate). Indeed, a textual absurdity (often) indicates a rhetorical trope; accordingly, the reader should interpret tropes not literally but figuratively. Second, I show that for Augustine, the inverse also holds true: the reader must interpret ad litteram those texts that are written properly (proprie dictum). In other words, Augustine used the absurdity criterion precisely to preserve Scripture’s literal, historical referent. I argue that in doing so, Augustine both distinguished himself from and implicitly critiqued the earlier tradition of allegorical interpretation. He cautions against taking passages that refer to literal referents as though they referred to nonliteral referents; and he warns against taking individual metaphors as entire allegorical narratives. I conclude by providing examples in which Augustine and Origen provide opposite interpretations of the very same biblical passages – Augustine preserving the text’s literal referent and Origen negating the text’s literal referent. Thus, Augustine’s interpretations offer a corrective to Origen’s earlier allegorical interpretations.